Journeying across borders in the science classroom: Do culturally relevant teaching/learning materials have a place? [PowerPoint presentation] - Coard, Maxine Keisha; George, June M. (My University, 2013)
This paper reports on a study that explored the process of border crossing between everyday experiences and a Form 4 biology class for three students in a secondary school in South Trinidad. The biology lessons were designed to include culturally relevant material from the students' home backgrounds with the expectation that this strategy would enhance border crossing. The paper describes and analyses how these three students, each representing a different level of academic achievement, manoeuvre across the cultural borders of the home and school. It follows their learning journey and details how each student experiences and responds to teacher-designed "bridge building" strategies using culturally relevant materials, both in terms of his/her level of interest in the biology class and his/her understanding of biology concepts. Data were collected via individual interviews, observations, and a post-unit achievement test. The findings revealed that the students responded in different ways to the introduction of culturally relevant material into the classroom and that all three students showed some change in achievement and interest. The paper explores the implications of the findings of this preliminary study for science education in Trinidad and Tobago. It points to the need for further research in this area since these preliminary results suggest that culturally relevant teaching/learning materials have some potential for facilitating the journey across borders
Paper presented at the Biennial Conference of The University of the West Indies Schools of Education, 23-25 April, 2013, St. Augustine, Trinidad and Tobago
Keywords: Biology education; Science education; Secondary school students; Secondary school science; Customs and traditions; Cultural factors; Teaching techniques; Conference papers; Trinidad and Tobago